The Development of Launch Methods for High Velocity Fragment Simulating Projectiles - Horsfall, Ian; McCamphill-Rose, P. J. (Cranfield University, 2013)
This paper describes the development of small-scale high velocity fragment launch methods which might be used to reproduce the effect of EFP-IED warheads. Two methods are described, both are capable of accurately delivering 50cal Fragment Simulating Projectile (FSP) to velocities in excess of 1500ms-1. The first method uses an explosive launcher to accelerate the projectile whilst the second method launches the saboted projectile from a gun. The explosive launch method allows relatively easy scale up to larger projectile sizes, and was capable of attaining a muzzle velocity of 1718ms-1 in the current series of tests. The gun launched method proved to be particularly controllable with respect to velocity (up to a maximum of 1832ms-1) but is more difficult to scale up.